2017
DOI: 10.1016/j.celrep.2017.09.071
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Determinants of Widespread Alternative Splicing Perturbation in Cancer

Abstract: SUMMARY It is increasingly appreciated that alternative splicing plays a key role in generating functional specificity and diversity in cancer. However, the mechanisms by which cancer mutations perturb splicing remain unknown. Here, we developed a network-based strategy, DrAS-Net, to investigate over 2.5 million variants across cancer types and link somatic mutations with cancer-specific splicing events. We identified over 40,000 driver variant candidates and their 80,000 putative splicing targets deregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 56 publications
0
41
0
Order By: Relevance
“…The downregulated RBPs were mainly enriched in the mRNA metabolic process, RNA processing, regulation of translation, TGF-beta signaling pathway, and Toll-like receptor signaling pathway. In recent years, a large number of studies, have reported the role of aberrant RNA metabolism and RNA processing in various diseases (Li et al, 2017(Li et al, , 2018Li S. et al, 2019;. RNA processing factors were shown to have increased expression in poorly differentiated non-small-cell lung cancer cells (Geles et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The downregulated RBPs were mainly enriched in the mRNA metabolic process, RNA processing, regulation of translation, TGF-beta signaling pathway, and Toll-like receptor signaling pathway. In recent years, a large number of studies, have reported the role of aberrant RNA metabolism and RNA processing in various diseases (Li et al, 2017(Li et al, , 2018Li S. et al, 2019;. RNA processing factors were shown to have increased expression in poorly differentiated non-small-cell lung cancer cells (Geles et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that deleterious mutations (including nonsense, missense, and even translationally silent mutations) residing within splicing regulatory regions exert effects on pre‐mRNA splicing in human diseases . For example, a recent pan‐cancer study revealed how point mutations can alter repertoires of splicing isoforms by connecting thousands of mutation‐splicing relationships across 33 types of cancer . Nevertheless, understanding of the dysregulation of splicing machinery components in HCC remains unclear.…”
mentioning
confidence: 99%
“…This computational framework has not only validated the experimental results observed in HCC but also provided insights into the RBP–gene regulatory networks across cancer types. In addition, alternative splicing (AS) is a process highly regulated by RBPs . Integration of AS data sets will provide novel insights into our understanding of RBP regulation in cancer.…”
Section: Discussionmentioning
confidence: 99%